Role of Radiofrequency Ablation in the Management of Unresectable Pancreatic Cancer - Yousaf, Muhammad Nadeem; Ehsan, Hamid; Muneeb, Ahmad; Wahab, Ahsan; Sana, Muhammad K.; Neupane, Karun; Chaudhary, Fizah S. (Frontiers in Medicine, 2021)
Pancreatic cancer is one of the most aggressive malignancies of the digestive tract and carries a poor prognosis. Majority of patients have advanced disease at the time of diagnosis. Surgical resection offers the only curative treatment but only a small proportion of patients can undergo surgical resection. Radiofrequency ablation (RFA) is a well-known modality in the management of solid organ tumors, however, its utility in the management of pancreatic cancer is under investigation. Since the past decade, there is increasing use of RFA as it provides a feasible palliation treatment in the management of unresectable pancreatic cancer. RFA causes tumor cytoreduction through multiple mechanisms such as coagulative necrosis, protein denaturation, and activation of anticancer immunity. The safety profile of RFA is controversial because of the high risk for complications, however, small prospective and retrospective studies have shown promising results in its applicability for palliative management of unresectable pancreatic malignancies. In this review, we discuss different approaches of RFA, their indications, technical accessibility, safety, and major complications in the management of unresectable pancreatic cancer.